PERBANDINGAN EFEKTIVITAS MADU ALAMI DENGAN MADU KEMASAN TERHADAP PEMUTIHAN GIGI SECARA IN VITRO - Wilda Sahroni; Elizabeth Bahar; Dedi Sumantri (Andalas Dental Journal, 2014)
Discoloration of teeth might be overcome by dental bleaching treatment. But the use of chemical bleaching agents caused a side effect. Therefore, many researchers were looking for alternative materials made from nature which is safer to used. Honey devided into 2 types, natural raw honey and packed honey, which both consist hydrogen peroxide (H2O2) that could whiten the teeeth. The purpose of this study was to compare the effectiveness of natural honey and packed honey for dental bleaching. This research was an in vitro experimental study with pre and post test control group design. 30 upper human premolar were used, devided into 3 groups based on bleaching agents used: 10 samples each group with application of natural honey, packed honey, and 10% carbamid peroxide. After application, samples were placed in incubator in 370C for 2 hours, then washed and soaked in artificiaal saliva, and incubated for 14 days. The colour change was observed by five observers using vitapan classical shade guide. The results of Kruskal-Wallis test showed p=0,000 witg significant value <0,05. Which means there was significant changes between before and after treatment. The average of tooth discoloration of 50% natural honey was 8,50, 50% packed honey was 7,30, and 10% carbamid peroxide as the contro group showed 10,10. In conclusion, natural honey was more effective in tooth whitening than packed honey.